Norma de auditoría gubernamental 407-04 evaluación de desempeño del personal y prestación de servicios de la empresa municipal terminal terrestre Quevedo, año 2013 - Mena Castillo, Andrea Carolina (2015)
This research was conducted with the administrative staff working in the Municipal Terminal Terrestre de Quevedo, for which surveys and interview was performed involved. The methods used were the inductive, deductive, analytic and synthetic, leading to the formulation of objectives to follow. The results show that there has never been a performance in the institution, there is ignorance about job descriptions. During the process of communicating the results to employees shows that almost always improvement plans are provided to correct weaknesses, should be those found in the process, due to the informality that communicated the results of the evaluation. The main benefits offered by the implementation of the process is that lets employees know their strengths and weaknesses. The 48.28% of administrators said that receives an interview "feedback orally", moreover 31.03% said receiving feedback "in writing and interview." This is because there is confusion in the population, and because the evaluator provides oral feedback to a certain part of the sample. The performance evaluation process applied to administrative staff develops certain weaknesses, for this reason the best results favoring the institution are not obtained, and allow more effectively and efficiently by staff.